Developing the gifted and talented young learner - Sutherland, Margaret, 1954- 4 0 16; 5 (Los Angeles : Sage, 2008)
Looks at how young children develop their beliefs about ability, focusing on gifted and talented children and their families, discusses issues involved in creating challenging activities for gifted youngsters, and includes sample activities related to stars, the sun, and space exploration.
Includes bibliographical references and index.
Professional;Professional
Keywords: 2 -- 0; 6; Education.;Education. -- Gifted children;Gifted children; 20; 2